Effect of adrenergic stimulation of the amygdaloid complex on water intake - Saad, W. A. [UNESP]; Bengtson, R. M. [UNESP]; De Arruda Camargo, L. A. [UNESP]; Renzi, Antonio [UNESP]; Vanderlei Menani, J. [UNESP]; Paulino, M. A. [UNESP] (My University, 1996)
The effect of noradrenaline, isoproterenol, phentolamine and propranolol, injected into the basolateral nuclei of the amygdala on water intake, was investigated in male Holtzman rats. The injection of noradrenaline (40 nmol) into the amygdaloid complex (AC) of satiated rats produced no change in water intake (0.05 ± 0.03 ml/1 hour). The injection of isoproterenol (40 nmol) produced an increase in water intake in sedated rats (1.93 ± 0.23 ml/1 hour). Noradrenaline injected into the AC produced a decrease in water intake in deprived rats (0.40 ± 0.19 ml/1 hour). The injection of isoproterenol into the AC of deprived rats produced no change in water intake in comparison with control (11.65 ± 1.02 and 10.92 ± 0.88 ml/1 hour, respectively). When compared with control values, phentolamine injected prior to noradrenaline blocked the inhibitory effect of noradrenaline on water intake in deprived rats (10.40 ± 1.31 ml/1 hour). Propranolol blocked the effect of isoproterenol in satiated rats (0.85 ± 0.49 ml/1 hour) and also blocked the water intake induced by deprivation (0.53 ± 0.38 ml/1 hour). In satiated and deprived animals the injection of phentolamine before hexamethonium blocked the inhibitory effect of hexamethonium on water intake. In satiated animals, when hexamethonium was injected alone, water intake was 0.39 ± 0.25 ml/1 hour and when hexamethonium was injected with phentolamine, water intake was 1.04 ± 0.3 ml/1 hour. In deprived animals, hexamethonium alone blocked water intake (0.40 ± 0.17 ml/1 hour) and when injected with phentolamine it elicited an intake of 9.7 ± 1.8 ml/1 hour. these results clearly demonstrate the participation of catecholaminergic receptors of the AC in the regulation of water intake.
Keywords: amygdaloid complex; drinking; receptors, adrenergic, alpha; receptors, adrenergic, beta; adrenergic receptor; hexamethonium; isoprenaline; noradrenalin; phentolamine; propranolol; adrenergic system; amygdaloid nucleus; animal experiment; fluid intake; male; nonhuman; water deprivation